Merevitalisasi UMKM Kabupaten Bekasi Melalui Transformasi Digital: Tinajuan PCA dan Analisis Spasial - Fauzi, Firman; Siregar, Hermanto; Barus, Baba; Indraprahasta, Galuh Syahbana (Badung Bali: Politeknik Negeri Bali, 2025)
Digital transformation is a pivotal factor in enhancing the competitiveness and resilience of Micro, Small, and Medium Enterprises (MSMEs). This study examines the key determinants influencing MSME digitalization in Kabupaten Bekasi through Principal Component Analysis (PCA) and spatial analysis. The PCA results identify five primary factors: individual readiness, organizational capability, cultural mindset, regulatory support, and ecosystem infrastructure. Spatial analysis employing the Moran’s Index and Local Indicator of Spatial Autocorrelation (LISA) reveals an uneven digital adoption pattern across 23 districts, forming four distinct clusters: High-High, High-Low, Low-High, and Low-Low.The findings underscore that MSME digitalization success is not solely contingent on individual readiness but is also shaped by institutional support, government policies, and the broader digital ecosystem. Consequently, a cluster-based digital transformation strategy is imperative: advanced clusters (High-High) should serve as role models, while lagging clusters (Low-Low) require targeted interventions, including infrastructure development and digital literacy initiatives. This study provides a robust foundation for policymakers to design more effective, evidence-based interventions aimed at fostering inclusive and sustainable MSME digitalization.